Platelet Large Cell Ratio as a Prothrombotic Biomarker to Predict the Severity of COVID-19 - Rikarni, Rikarni; Najirman, Najirman; Yulia, Dwi; Burhan, Ida Rahmah; Amalina (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the lungs causes alveolar cell inflammation and disruption, leading to increased levels of proinflammatory cytokines that stimulate platelet activation and consumption. In response, megakaryocytes will increase the production of large, immature platelets. Large platelets bind more to fibrinogen than small platelets, increasing the potential for thrombus formation. This study aims to analyze the platelet large cell ratio as a prothrombotic biomarker to predict the severity of thrombosis in patients. A prospective cohort study was conducted in May-November 2021 at M. Djamil Hospital involving 206 samples of confirmed coronavirus disease 2019 (COVID-19) patients. The examinations included platelet count, P-LCR, and D-dimer. Large platelet counts were calculated using the Platelet Large Cell Ratio (P-LCR) parameter with an automated hematology analyzer. Clinical manifestations of disease severity were monitored based on WHO criteria, grouped into non-severe and severe disease. The 3 results showed a mean age of 47.41 (SD = 17.82). Platelet count was 263,690 (116,995)/mm , P-LCR was 30.86 (6.63)%, and D-dimer value was 2,215.97 (2,590.86) ng/mL. The P-LCR in the severe group was 35.08 (8.21)%, and the non-severe group was 26.64 (6.81)%, with p <0.001. D-dimer in the severe group was 3,680.36 (3,006.23) ng/mL, and in the non-severe group, 869.12 (977.03) ng/mL, with p <0.001. The relative risk of a high P-LCR causing severe COVID-19 is 2.35 compared to a low P-LCR, with p <0.001. The relative risk of a high D-dimer value causing severe COVID-19 is 6.80 compared to a low D-dimer, with p <0.001. The conclusion is  that a greater increase in large platelet production occurs in severe COVID-19 disease. P-LCR is a crucial biomarker for evaluating platelet activity. A high P-LCR value is a risk factor for predicting the severity of COVID-19. Suggestions for the use of PLCR. Increased risk of thrombotic events in COVID-19 patients can be identified by P-LCR examination upon admission to the hospital, allowing for preventive treatment.